Improving SDOH Screening in an Inpatient Setting - Barrett Odom (My University, 2025)
Abstract Aim: This study aimed to determine if the implementation of an educational toolkit for nurses improved social determinants of health (SDOH) screening compliance on an inpatient unit. The overarching goal was to increase identification of those with SDOH needs and to address those needs. Design: A quantitative design was used. Methods: A toolkit was developed to educate nurses on a 24-bed unit on SDOH and screening for SDOH. A total of 323 patients were admitted to the study unit, where 49 nurses are employed. The study evaluated the number of patients who were screened for SDOH needs upon admission to the unit, as well as nursing perception of SDOH and SDOH screening with two surveys. The goal was to improve SDOH screening by 10%. Results: Survey results indicate nurses thought the toolkit was helpful; however, SDOH screening rates increased by only 1.8%. Conclusion: Although the educational toolkit was well-received, other methods are needed to improve SDOH screening rates in an inpatient setting. Implications: Further studies are necessary to address SDOH screening compliance. Possible realms of improvement include streamlined screening forms and several on-site nurse champions. Impact: SDOH plays a large role in people’s health and well-being. Addressing SDOH needs can improve patient outcomes and the health of the community. Even a small increase in screening rates is impactful, although further studies are needed to make a lasting impact on SDOH screening. Contribution: There were no patient or public contributions. Contribution to the Clinical Community: This study ameliorates a paucity in research surrounding SDOH screening and improving SDOH screening compliance.
Improving SDOH Screening in an Inpatient Setting: A Quality Improvement Study
Keywords: SDOH; Social determinants of health; toolkit; screening; inpatient